Thrombocyte volume parameters in different disease groups - Akarsu, Saadet; Kurt, A. Nese Citak; Kurt, Abdullah; Varol, Ilknur; Sen, Yasar (Aves, 2006)
Aim: We aimed to determine the values of thrombocyte volume parameters (mean platelet volume (MPV(, platelet distribution width (PDW() in different diseases. In this way, we aimed to ensure differential diagnosis in the diseases directly caused by bone marrow during the diagnosis process and to determine the effects of the systemic diseases on thrombocytes. Material and Method: The records of 452 acute or chronic cases who have been followed in our clinic for three years were reviewed retrospectively. The cases were divided into three groups as hematological diseases, systemic diseases and intoxications. Results: Of the 452 patients taken into this study, 245 (54%) were boys, 207 (46%) were girls. The medium age of the patients was 87.1 +/- 58.2 (1-216) months. The MPV values were determined to be as 7.6 +/- 1.4, 7.8 +/- 1.1, 7.2 +/- 1.0, 8.2 +/- 1.4, 6.7 +/- 0.4 and 7.8 +/- 1.5 fl in hematological, cardiac, nephrological, endocrinological, allergic diseases, and intoxications, respectively. There was not a significant difference among the groups for MPV (p(0.05). PDW value was determined to be as 14.6 +/- 3.1, 17.6 +/- 4.0, 17.8 +/- 5.7, 16.4 +/- 1.8, 15.9 +/- 0.5 and 16.9 +/- 0.6 fl in hematological, cardiac, nephrological, endocrinological, allergic diseases, and intoxications respectively. There were significant statistical differences for PDW values between hematological and systemic diseases or intoxications (p(0.05). Conclusions: Additional studies, those include higher number of patients and those evaluate PDW values especially in hematological diseases might require. It is a remarkable fact that PDW values of thrombocytes is very important in differential diagnosis.
De?işik hastalik gruplarinda trombosit hacim de?işkenleri
Keywords: clinical disorders; mean platelet volume; platelet distribution width; platelet volume parameters